Transfer of Image and Character in Artistic Translation - Kakhramonov Jakhongir Boymakhmat Ugli; Abdurakhmon Norinboev (International Journal on Integrated Education, 2022)
This article provides information about the human image and its depiction in translations.The contributions of Leyden, Erskine, Kaiser and Klaproth in the translation of Z.M. Babur's works into European languages are huge. The services of G. Salomov, N. Otajonov, G. Khojayev and others in studying the translations of Babur's work into European languages and showing his place in world literature are worthy of praise, but a special research work on the presentation of image and character in artistic translation not done.